Melissopalynological analysis and plant preferences of stingless bee, Heterotrigona itama (Hymenoptera: Apidae) at the Malaysian Agricultural Research and Development Institute (Mardi), Serdang - Sumaya Rahmatullah,; Muhammad Amirul Aiman Ahmad Juhari,; Mohd Fahimee Jaapar,; Balqis Mohamad,; Mohamad Nurmirza Samion, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Melissopalynology plays a pivotal role in ecological studies by identifying floral sources for honeybee nutrition and contributes to a better understanding of plant-pollinator interactions. It is essential for biodiversity monitoring, conservation efforts, and assessing the quality and authenticity of honey products based on pollen analysis. This study investigates the melissopalynological of honey samples collected from stingless bee species Heterotrigona itama (Hymenoptera: Apidae) at the Malaysian Agricultural Research and Development Institute (MARDI). A total of 17 flower samples and 10 mL of honey were collected from one beehive and further analyzed using a light microscope. The analysis identified eight pollen types from eight distinct plant species from the honey sample. Clematis crispa was the most prominent, representing 21.74% of the total pollen count, followed by Combretum indicum (17.39%) and Cucumis sativus (17.39%). Lagerstroemia speciosa contributed 13.04%, Ageratum conyzoides and Averrhoa bilimbi each accounted for 8.70%, while Ipomoea purpurea and Clitoria ternatea contributed 8.70% and 4.35%, respectively. The results highlight the floral preferences of H. itama bee at MARDI. This comprehensive melissopalynological analysis contributes to biodiversity monitoring and conservation efforts by providing a better understanding of the floral resources used by stingless bee species in the MARDI ecosystem.